A way out of the credibility crisis of models used in integrated environmental assessment. - Sluijs, Jeroen P. van der (Futures, 2002)
Integrated Assessment Models (IAMs) have been widely used in environmental policy making because they simulate natural and socio-economic systems by integrating knowledge derived from a wide range of disciplines. The current IAMs have been found to be limited due to their inability to display both the value-laden nature of the assumptions that underlie the model and the uncertainties in their outputs. A Post-Normal Science approach is required for dealing with these issues, involving participation of 'extended peer communities' providing their 'extended facts'. Copyright (c) 2001 Elsevier Science Ltd